Blindsided ebook - Michaels, Fern (Sisterhood, 2013)
Count on the Sisterhood to skirt the law in the name of justice. From the #1 New York Times bestselling author of Gotcha! Myra Rutledge isn't ready to mothball the Sisterhood just yet. When Maggie Spitzer, former editor-in-chief of the Post and an honorary member of the Sisterhood, arrives with a new mission in mind, the Vigilantes are soon gathering in their war room once more. While catching up on each other's lives, they plan a brilliant campaign against a duo of corrupt judges running a moneymaking racket that sends young offenders to brutal boot camps, often on trumped-up charges. Their enemies are powerful and ruthless, but the Sisterhood have their own formidable allies—including former President Martine Connor. Once their scheme takes off, the guilty won't know what hit them . . . Series praise "Spunky women who fight for truth, justice, and the American way."— Fresh Fiction on Final Justice "Readers will enjoy seeing what happens when well-funded, very angry women take the law into their own hands."— Booklist on Weekend Warriors "Delectable . . . deliver[s] revenge that's creatively swift and sweet, Michaels-style."— Publishers Weekly on Hokus Pokus